Pengaruh Dukungan Kader dalam Imunisasi Dasar Lengkap di wilayah kerja Puskesmas Jelbuk dan Klatakan, Kabupaten Jember - Widya Rizki Septianingtyas; FX. Ady Soesetijo; Ristya Widi E. Y (Pascasarjana Universitas Jember, 2018)
Immunization is an attempt to actively generate or enhance a person's immunity to a disease, so that when exposed to the disease will not experience pain or only mild illness. Immunization program for baby aims to make every baby get immunization basic complete. The successfull of baby in obtaining basic immunization can be measured by complete basic immunization indicator (IDL). Basic immunization status on the children can be influenced by several factors associated with people behavior. Cadre's support is one of the important factors in immunization activities so that Posyandu activities can work as on schedule. Jelbuk and Klatakan public health center have complete basic immunization coverage lowest in Jember district in 2015 and 2016 years. The aim of this research was to analyze the influence of cadre’s support in the complete basic immunization. This research used analytic observational with cross Sectional analysis design. The location of this research was in the working area Jelbuk and Klatakan public health center on August – September 2017. The data was collected from 100 mothers who has children aged 12-23 months. Sampling method was using cluster random sampling. The results of this research by the logistic regression test showed that cadre support has an influence on complete basic immunization with p-value= 0,013. Therefore, its recommended for cadres to improve public education about complete basic immunization so that complete basic immunization coverage may increase. Keywords : Cadre’s Support, Complete Basic Immunization